Micromegas detector response test at the new EAR2 neutron beam of n_TOF facility in view of the 243Am(n,f) measurement - Kyritsis, Nikolaos; Diakaki, Maria; Michalopoulou, Veatriki; Eleme, Zinovia; Patronis, Nikolaos; Kokkoris , Michael; Vlastou, Roza; n_TOF collaboration (HNPS Advances in Nuclear Physics, 2024)
A key ingredient of the design of advanced nuclear systems, such as Generation IV reactors and accelerator driven systems, is the study of neutron induced fission reactions. Accurate cross-section data on key actinides is needed both for their operation and the handling of the nuclear waste. 243Am is among the long-lived isotopes present in nuclear wastes, that contribute to the long-term radiotoxicity, and the respective fission cross-section data are needed with high accuracies. Consequently, an experiment was planned to measure the neutron induced fission cross section of 243Am in experimental areas EAR1 and EAR2 the n_TOF facility at CERN. However, due to the change of the lead spallation target of the n_TOF facility, which led to significant changes in the characteristics of the neutron beam of experimental area EAR2, as well as to the increased complexity of the setup compared to similar past experiments, a preliminary experiment to test the setup in the new conditions was deemed necessary. In this work, we will describe the experimental setup and examine the test results.